Social Development and Higher Education - España Chavarría, Carolina (Revista Electrónica Educare, 2011)
This essay has as its main objective to reflect on the duty of the Costa Rican public university and its responsibility to educate in order to foster social development, which is understood as one of the multiple challenges that the higher education faces due to the demands imposed on the operation of knowledge in the present and the relation of such demands with independent knowledge development. In addition, a defense is made of some issues that have been approached weakly in previous studies, issues that become part of the essential elements for promoting a meaningful and functional education that has social impact, elements such as the following: a) Ethics in the organization, b) The university’s self-education, c) The effect of curricular policies on the practices being promoted, d) The transformation of the teaching culture to improve practice, and e) The construction of knowledge on which to base criteria, decision making, problem solving and the development of life projects.